130nm DC-DC SEPIC Design and ,Analysis for Energy Harvesting Applications - Guzeltepe, Ismail; Vural, Revna Acar; Batur, Okan Zafer (IEEE, 2020)
SEPIC converters, which are becoming widespread in several areas, including renewable energy; are often preferred due to non-inverted output, non-excessive switch stress and considerably less input current ripple. However, there are not enough studies in the literature on the use of the SEPIC converters in ultra-low voltage applications. In this study; It is aimed to design the effective use of DC-DC SEPIC converters consisting of integrated active components for very low voltage energy harvesting applications. In this context; using UMC 130nm technology; A DC-DC SEPIC converter, capable of providing a constant IV output with an input voltage range of 150mV-1.6V and offering an output power range of 1.3-7.7mW with 80% efficiency, has been designed and analyzed.
12th International Conference on Electrical and Electronics Engineering (ELECO) -- NOV 26-28, 2020 -- Bursa, TURKEY